Motivational Drivers in English for Academic Purposes: Teaching, Texts and Tasks - Pandey, Gopal Prasad (International Journal of Social Sciences and Management, 2025)
This paper explores the motivational factors that enhance student engagement in English for Academic Purposes (EAP) reading, focusing on its significance in equipping learners with essential academic skills, particularly in context of Tribhuvan University, Nepal. Using a qualitative descriptive approach, the research involved semi-structured interviews with four experienced English teachers to understand the challenges and strategies influencing learner motivation. The findings reveal that well-structured texts, alignment with academic goals, and the integration of visuals significantly boost engagement, while reliance on alternative resources and complex academic texts pose challenges. Effective teaching strategies, such as scaffolding, first-language explanations and interactive tasks, were highlighted as crucial for fostering motivation. Furthermore, aligning assessments with classroom activities was found to build trust and sustain student effort. The study highlights the role of instructional practices and contextual factors in shaping learner motivation and offers practical implications for improving EAP instruction. By emphasizing relevance, interactivity and support, this research contributes to enhancing teaching strategies and addressing motivational gaps in EAP settings. Future studies are recommended to explore learner perspectives and the long-term effects of these strategies on academic engagement and proficiency. Int. J. Soc. Sc. Manage. Vol. 12, Issue-1: 18-26.